Organizational culture as core of business performance : A study of Japanese MNC's in Malaysia / Musleena Mustapha - Musleena, Mustapha (2012)
Many developing countries compete to attract Multinational Companies (MNCs) due to their potentially significant contribution towards a more productive economic growth. Emerging Asian economic powerhouses like China, Thailand and Malaysia are constantly under the radar of many MNCs from developed countries such as the United States, European Union and East Asian giants like Japan and South Korea. MNC rides on the wave of globalization and ply their trade through direct foreign investment or establishing subsidiaries to optimize their shareholders equity. However, the MNCs economic contribution overshadows certain socio-cultural impact on the host country, and the MNC itself in terms of business performance. The impact of an Asian local culture and its attribution to organizational culture and business performance of a foreign MNC is an interesting phenomenon which not many studies have been conducted. Hence the purpose of this study is to investigate the possible relationships between organizational culture of a host country, Malaysia and business performance of the Japanese MNC based on Hofstede’s four main cultural dimensions; individualism vs collectivism, power distance, uncertainty avoidance and masculinity vs femininity (Hofstede, 1980). It is a common scenario that foreign companies in the developing countries are managed or headed by expatriate managers from the MNC home country (Raduan Che Rose, 2008). Patrick, Felicitas and Albaum (2005) maintained that the management styles adopted by the expatriate managers are in accordance to the corporate culture of their home country. The organizational culture indicators of the Japanese MNC’s profile were used as for items in the research instruments per culture impact on a variety of organizational processes and performance. The respondents were drawn from executive and managerial level from Japanese MNC’s operated more than 10 years in Malaysia, with more than 3000 total employees in electronic and high tech industries. The findings of this study have demonstrated the influence of culture in determining organizational business performance.